Coarse Correlated Equilibria in an Abatement Game - Herve Moulin; Indrajit Ray; Sonali Sen Gupta (Cardiff University, Cardiff Business School, 2014)
We consider the well-analyzed abatement game (Barrett 1994) and prove that correlation among the players (nations) can strictly improve upon the Nash equilibrium payoffs. As these games are potential games, correlated equilibrium - CE - (Aumann 1974, 1987) cannot improve upon Nash; however we prove that coarse correlated equilibria - CCE - (Moulin and Vial 1978) may do so. We compute the largest feasible total utility and hence the efficiency gain in any CCE in those games: it is achieved by a lottery over only two pure strategy profiles.
Keywords: C72; Q52; 330; Abatement game; Coarse correlated equilibrium; Efficiency gain